Terrestrial ages of seven meteorite strewn fields and two single unpaired meteorites from the Sultanate of Oman determined using 14C and 10Be. (13th November 2022) - Sliz, Malgorzata U.; Hofmann, Beda A.; Leya, Ingo; Szidat, Sönke; Espic, Christophe; Gattacceca, Jérôme; Braucher, Régis; Borschneck, Daniel; Gnos, Edwin; ,
Abstract: Through the investigation of terrestrial ages of meteorites from Oman, we aim to better understand the time scales of meteorite accumulation and erosion in Oman and the meteorite flux in the past. Here, we present 14 C and 14 C‐ 10 Be terrestrial ages of seven ordinary chondrite strewn fields and two unpaired single meteorites from the Sultanate of Oman. After critical evaluation of multiple data for each strewn field, we propose "best estimate terrestrial ages, " typically based on 14 C/ 10 Be. For objects for which complex irradiation histories are known or suspected, terrestrial ages were calculated solely using 14 C. The best estimate strewn field ages range from 8.1 ± 3.0 ka (SaU 001) to 35.2 ± 5.1 ka (Dho 005). Including two previously dated strewn fields, the mean and median age of nine Oman strewn fields is 15.9 ± 12.3 and 13.6 ka, respectively. The new data show a general good agreement with data previously obtained in a different laboratory, and we observe a similar general correlation between strewn field ages and mean weathering grade as in previous work based on individual meteorites. Weathering degree W4 is reached for dated samples after 20–35 ka. While the age statistics of strewn fields does not show the previously observed lack of young events, the low abundance of young (0–5 ka) individual meteorites as compared with older ( 20 ka) meteorites is confirmed by our data and remains unexplained.